Model Pendidikan Pesantren: Studi Kasus di Pesantren Rakyat Al-Amin Sumberpucung Kab. Malang - Ianatut Thoifah (Universitas Muhammadiyah Malang, 2018)
System is a set of elements of education which are related and connected each other and give influence each other to achieve a certain goal. One of attempt that can be done is through developing system of Islamic Education there, while the model is a product of developing system. Focus of this research is how implementation of the model “Rakyat Al- Amin” Islamic boarding school in Sumberpucung, Malang including some components of Islamic boarding school itself: boarding, mosque, Islamic classic books, students and kiyai. The result of this research shows the difference of the components of Islamic boarding school commonly and the components of Rakyat Islamic boarding school. In the reality Rakyat Islamic boarding school only has 3 components such as teaching Islamic classic book, students and kyai, but it doesn’t mean that the other components of Islamic boarding school are not important, the other components just have different function.